Investigation into the subcellular localisation and function of miR-122 - Winlow, Poppy (2021)
MicroRNAs are key post-transcriptional regulators of gene expression and function either by translational repression or degradation of target mRNAs. To do so, microRNAs must form an RNA-induced silencing complex (RISC) and direct its binding to the 3’ UTR of their target mRNAs. Whilst the understanding of microRNA function has been extensively investigated, there has been little research on whether this differs in subcellular locations.